Long-term trends in the socio-economic development of Arab countries - V. A. Meliantsev (Vestnik MGIMO-Universiteta, 2020)
Abstract: The article analyzes a number of the most important trends, proportions and factors of the economic and social development of the Arab countries over the past four decades, associated with the modern stage of globalization, against the background of other countries and a deeper retrospective view. It reveals the extent of Arab countries’ convergence, as well as divergence in the levels of technological, economic and social development with/from leading regions and countries of the developing world and economically advanced states. With all the considerable differentiation that exists between Arab countries in the 1980-2010s, in contrast to a number of other countries and regions of the East and South, the Arab world on the whole has suffered from a significant slowdown in the dynamics of per capita GDP, total factor productivity, human development index and augmented development index.These trends, according to the author’s calculations, are determined not only and not so much by high population growth rates, but by the limited nature of economic and institutional reforms that affect the degree of diversification of production and export structures, share of investments in physical and human capital in GDP, and the quality of labor. Moreover, according to new data and author’s calculations, the level of inequality in income distributionin the Arab world is one of the highest in the world. This and other factors, including geopolitical ones, as well as the increasing number of so-called “failing states” in the region have brought about an increase in socio-political tensions, which is comparable, and even exceeding the level that existed a decade ago, when the Arab Spring phenomenon arose.Under pandemic and global crisis, the economic and social situation in a number of Arab countries is markedly getting worse. In order to ease tensions in the region it is high time to implement a number of reforms aimed at mitigating inequality and simultaneously increasing the purchasing power of the population and expanding domestic markets as well as creating much more favorable investment climate.